2014
DOI: 10.1371/journal.pone.0087451
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Circulating MicroRNA Signature for Colorectal Cancer Detection

Abstract: Prognosis of patients with colorectal cancer (CRC) is generally poor because of the lack of simple, convenient, and noninvasive tools for CRC detection at the early stage. The discovery of microRNAs (miRNAs) and their different expression profiles among different kinds of diseases has opened a new avenue for tumor diagnosis. We built a serum microRNA expression profile signature and tested its specificity and sensitivity as a biomarker in the diagnosis of CRC. We also studied its possible role in monitoring th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
112
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(121 citation statements)
references
References 35 publications
7
112
1
1
Order By: Relevance
“…In addition, this signature could be used in combination with other noninvasive biomarkers. Several research groups showed a rise in sensitivity by combining microRNA signatures with the detection of the carcinoembryonic antigen (CEA) [23,48]. Thus, in combination with other potential tumor markers this five microRNA signatures could be a powerful tool in the noninvasive diagnostic of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this signature could be used in combination with other noninvasive biomarkers. Several research groups showed a rise in sensitivity by combining microRNA signatures with the detection of the carcinoembryonic antigen (CEA) [23,48]. Thus, in combination with other potential tumor markers this five microRNA signatures could be a powerful tool in the noninvasive diagnostic of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence suggesting that circulating miRNAs can contribute to tumorigenesis by modulating oncogenic or tumor suppressor pathways 22,10 . Several studies have compared the expression profiles of miRNAs in serum or plasma across a variety of tumours to identify cancer-specific expression patterns: data obtained suggested that circulating miRNAs expression could be used to discriminate disease samples, demonstrating their potential use as blood-based diagnostic cancer markers [23][24][25][26] .…”
Section: Mirna Alterations In Um Vh and Exosomes Significantly Overlapmentioning
confidence: 99%
“…candidate biomarkers for CRC diagnosis, miR-92a was down-regulated in CRC than control samples [18]. The similar contradictory results were also observed in the circulating miRNAs miR-145, miR-150 and miR-203 [19][20][21][22].…”
Section: Main Circulating Mirnas In Crc Diagnosismentioning
confidence: 54%